In Vitro and In Silico Acetylcholinesterase Inhibitory Activity of Thalictricavine and Canadine and Their Predicted Penetration across the Blood-Brain Barrier - Chlebek, Jakub; Korabecny, Jan; Dolezal, Rafael; Štěpánková, Šárka; Perez, Daniel I.; Hostalkova, Anna; Opletal, Lubomir; Cahlikova, Lucie; Macakova, Katerina; Kucera, Tomas; Hrabinova, Martina; Jun, Daniel (MDPI AG (Multidisciplinary Digital Publishing Institute), 2019)
In recent studies, several alkaloids acting as cholinesterase inhibitors were isolated from Corydalis cava (Papaveraceae). Inhibitory activities of (+)-thalictricavine (1) and (+)-canadine (2) on human acetylcholinesterase (hAChE) and butyrylcholinesterase (hBChE) were evaluated with the Ellman's spectrophotometric method. Molecular modeling was used to inspect the binding mode of compounds into the active site pocket of hAChE. The possible permeability of 1 and 2 through the blood-brain barrier (BBB) was predicted by the parallel artificial permeation assay (PAMPA) and logBB calculation. In vitro, 1 and 2 were found to be selective hAChE inhibitors with IC50 values of 0.38 +/- 0.05 mu M and 0.70 +/- 0.07 mu M, respectively, but against hBChE were considered inactive (IC50 values > 100 mu M). Furthermore, both alkaloids demonstrated a competitive-type pattern of hAChE inhibition and bind, most probably, in the same AChE sub-site as its substrate. In silico docking experiments allowed us to confirm their binding poses into the active center of hAChE. Based on the PAMPA and logBB calculation, 2 is potentially centrally active, but for 1 BBB crossing is limited. In conclusion, 1 and 2 appear as potential lead compounds for the treatment of Alzheimer's disease.
In vitro a in silico stanovení inhibiční aktivity thaliktrikavinu a kanadinu vůči acetylcholinesteráze a odhad jejich přestupu přes hematoencefalickou bariéru
Keywords: (+)-thalictricavine; (+)-canadine; cholinesterases; kinetic study; molecular docking; blood-brain barrier permeability; (+)-thaliktrikavin; (+)-kanadin; cholinesterázy; kinetické studie; molekulární docking; přechod hematoencefalickou bariérou